2015
DOI: 10.1123/japa.2014-0128
|View full text |Cite
|
Sign up to set email alerts
|

Views From the Path: Evaluating Physical Activity Use Patterns and Design Preferences of Older Adults on the Bolin Creek Greenway Trail

Abstract: Though physical inactivity can lead to increased health problems in older adults, few places actually encourage this population to be active by implementing choices that allow the built and natural environment to be accessed by foot or bicycle. In addition, little research has examined older adults' perceptions of design and the relationship between greenways and improving public health, a topic that is receiving popular attention. The objective of this mixed-methods study was therefore to evaluate elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The user survey results also showed that the audience of the trail is mainly residents of nearby communities, and approximately 78% of users visit on foot or by bike. This result is relatively consistent with the preference research results of Dorwart et al and Keith et al on the use of greenway trails, with trail visitors being mainly nearby residents [62,64].…”
Section: Promotion Of Healthy Travelsupporting
confidence: 92%
See 1 more Smart Citation
“…The user survey results also showed that the audience of the trail is mainly residents of nearby communities, and approximately 78% of users visit on foot or by bike. This result is relatively consistent with the preference research results of Dorwart et al and Keith et al on the use of greenway trails, with trail visitors being mainly nearby residents [62,64].…”
Section: Promotion Of Healthy Travelsupporting
confidence: 92%
“…An IPA evaluation of the Atlanta Loop Greenway in Georgia, USA also found that residents were dissatisfied with various forms of safety elements on greenways [34], and the evaluation of the use patterns of and design preferences for sports activities for elderly people on the Berlin Creek Greenway also reflected care for vulnerable groups [64]. Therefore, in addition to adopting the complete service facilities mentioned earlier, attention should be paid to night lighting and to ensuring the continuity of routes.…”
Section: Trail Attributes Affecting the Health Promotion Of Country G...mentioning
confidence: 99%
“…Unsurprisingly, older adults will make their own risk assessment and avoid those environments seen as risking falls and/or their physical safety. Easily accessible and low-cost recreational facilities that provide age-appropriate group activities are preferred by older adults and air-conditioned indoor gyms and pools may be particularly favoured in high temperatures [69,70]. One review highlighted that one specific recreational facility appears to be insufficient and a mixture of age-friendly recreational facilities which could include parks and open spaces is preferable to allow older adults to engage in multiple potential forms of physical ac-tivities/sports, such as walking, cycling and other sports (tai chi, dancing, etc.)…”
Section: Physical Environmentmentioning
confidence: 99%